Resource element-level dimensioning of long term evolution networks - Oudah, Arshed (Universiti Utara Malaysia Press, 2013)
Long Term Evolution (LTE) of Universal Mobile Telecommunications System (UMTS) is the latest cellular technology coined by the third Generation Partnership Project (3GPP) and is currently being deployed worldwide.a crucial step towards the successful deployment scenarios of LTE networks is through the use of accurate budgetary and coverage dimensioning formulas of LTE’s physical air-interface channels and signals to guarantee favourable cell footprint and other capacity targets. In this paper, the total physical downlink resources along with their associated powers are derived and computed. Their corresponding overheads are also presented.The provided formulas serve in various network dimensioning campaigns of the LTE systems.